EDUCATION NATIONAL CONSCIOUSNESS OF YOUTH IN THE EUROPEAN INTEGRATION OF UKRAINE - Holovchuk, Svitlana Y. (Educological discourse, 2014)
The peculiarities of the national consciousness of youth education in conditions of Ukraine's European integration; disclosed the meaning of "patriotism" as a social and moral principles of activity relationship to his people, reflecting national pride and love for the country, the civil liability for its destiny, as well as emotional subordinate personalities of their lives overall national interests and is manifested in the willingness to serve the motherland.